2014
DOI: 10.1149/2.012407jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Formation of Pr–Ni Alloys in LiF–CaF2–PrF3and NaCl–KCl–PrCl3Melts

Abstract: For the establishment of a process for the electrochemical recovery of rare earth elements from used magnet scraps, the electrochemical formation of Pr-Ni alloys in molten LiF-CaF 2 -PrF 3 and NaCl-KCl-PrCl 3 salts at 1123 K and 973 K, respectively, was investigated.Cyclic voltammetry and open-circuit potentiometry indicated the formation of several phases of Pr-Ni alloys. Alloy samples were prepared by one-or two-step potentiostatic electrolysis using a Ni plate electrode at various potentials. Scanning elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 19 publications
2
35
0
Order By: Relevance
“…Table 1 Formation reactions and corresponding potentials for RE-Ni alloys and RE metals in molten NaCl-KCl-0.50 mol%RECl 3 at 973 K (RE = Pr, Nd, and Dy). [13][14][15]…”
Section: Mechanism For Formation Of Re-ni Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 Formation reactions and corresponding potentials for RE-Ni alloys and RE metals in molten NaCl-KCl-0.50 mol%RECl 3 at 973 K (RE = Pr, Nd, and Dy). [13][14][15]…”
Section: Mechanism For Formation Of Re-ni Alloysmentioning
confidence: 99%
“…salts at 1123 K [10][11][12]15 and molten NaCl-KCl-RECl 3 salts at 973 K. [13][14][15] Concerning the LiF-CaF 2 eutectic melt, Nourry et al also reported the formations of Nd-Ni alloys. 16,17 For the application of the process, investigations not only of the behaviors of each element but also of the separation between Pr, Nd, and Dy are essential.…”
Section: Introductionmentioning
confidence: 99%
“…The first one is the formation of different RE‐iron group(IG) alloys for preparation of magnetic materials . Nohira et al ,. investigated the electrochemical formation and phase control of Pr−Ni alloys in LiCl‐KCl‐PrCl 3 melts, LiF‐CaF 2 ‐PrF 3 and NaCl‐KCl‐PrCl 3 melts.…”
Section: Introductionmentioning
confidence: 99%
“…We have proposed a new separation and recovery process for RE elements from magnet scraps using molten salt electrochemistry utilizing an alloy diaphragm. [9][10][11][12][13][14][15] In the proposed process, two molten salt electrolytes are separated by an RE-iron group (IG) alloy diaphragm. Scraps of RE magnets are used as an anode to dissolve RE elements into the molten salt in the anode chamber, and then, Pr, Nd, and Dy are separated using the differences in both the formation potentials and formation rates of the RE-IG alloys.…”
Section: Introductionmentioning
confidence: 99%
“…salts at 1123 K [10][11][12]15 and molten NaCl-KCl-RECl 3 salts at 973 K. [13][14][15] Concerning the LiF-CaF 2 eutectic melt, Nourry et al also reported the formations of Nd-Ni alloys. 16,17 For the application of the process, investigations not only of the behaviors of each element but also of the separation between Pr, Nd, and Dy are essential.…”
Section: Introductionmentioning
confidence: 99%